The effectiveness of common disinfection procedures for gutta percha points - Asprer, Meredith M.
The effectiveness of disinfection procedures for gutta perca points in endodontics was investigated. Four disinfection solutions were used in six different ways. The ease and practicality of the formocresol vapor technique makes it the one of choice.